Research Activity on Medicago Spp. at the 'Istituto Sperimentale per la Colture Foraggere', Lodi-Italy - Rotili P.; Berardo N.; Gnocchi G.; Pecetti L.; Piano E.; Scotti C. (The Genus Medicago in the Mediterranean region: Current situation and prospects in research, 1996)
In the last 15 years new lucerne cultivars were released by ISCF, Lodi. The variety constitution process is characterized by: i) the exploitation of the effects of biological density (competition) in the phenotypic evaluation; ii) the utilization of a selfing phase in the breeding schemes; and iii) a variety model based on a little number of partly inbred parental clones from genetically distant populations. In framing breeding procedures, the conceptual guideline of lucerne 'stand system' has been elaborated, where plants are the constitutive elements and their spatial organization and degree of interference represent the 'structure' of the system. Breeding procedures aim at improving both plants and structure. A plant model has been developed aimed at direct improvement of vigour and enhanced persistence. Development of free-hybrid varieties has been proposed to exploit both additive and heterotic effects. Investigations are in progress to assess the value of different free-hybrid models relative to the corresponding synthetic varieties. Established results suggest that direct selection for protein and fibre content is expected to be ineffective. Indirect selection for quality through physiological characters appears more appropriate. Assessment of lucerne-Rhizobium meliloti relationships have been integrated into the breeding schemes for improvement of plant symbiotic ability. Use of molecular markers has been recently implemented to estimate plant heterozygosity levels with the objective of individuating genotypes which combine high vigour and low heterozygosity. A breeding project aimed at developing creeping-rooted or rhizomatous lucerne varieties suited to grazing has also been activated. This involved the evaluation of morphological traits in wide collections from the Medicago sativa complex.
Meeting of the Mediterranean Working Group on Medicago of the FAO/CIHEAM Inter-Regional Research and Development Network on Pastures and Fodder Crops, 1995/10/19-22, Hammamet (Tunisia)